UV-B and abscisic acid effects on grape berry maturation and quality - Berli, Federico Javier (2013)
This review provides an overview of existing literature on the effects of ultraviolet-B (UV-B) radiation and abscisic acid (ABA) on physiological and biochemical aspects affecting grape berry (Vitis vinifera L.) growth, maturation and their quality for winemaking. The UV-B (280?315 nm) comprises only a small fraction of sunlight that reaches the Earth?s surface, but has enough energy to cause large photobiological effects on higher plants. The UV-B levels are greater in the tropics than in upper latitudes and also increase with altitude, hence some vineyards are exposed to high UV-B but photoprotection and repair mechanisms are usually sufficient to prevent the occurrence of damage in grapevine tissues. ABA is a phytohormone that, aside to control stomatal aperture, regulates acclimation to adverse environmental conditions, and controls grape berry maturation (non-climacteric). A promotive effect of UV-B on ABA biosynthesis has been found in grapevine leaves. Accumulation of phenols (namely phenolic acids, stilbenes and flavonoids) is an acclimation and protective response against UV-B, either directly by absorbing UV-B in epidermal tissues and/or by reducing its penetration through underlying tissues, or indirectly by scavenging free radicals so acting as antioxidants. High UV-B and ABA applications increase total phenols in grape berries, but those with higher antioxidant capacity (i.e. dihydroxylated anthocyanidins and flavonols like quercetin) are increased relatively more. These treatments also hasten berry sugar and phenol accumulation, but reduce berry growth and sugar per berry at harvest, and therefore decrease yield. The quality of grape berries for winemaking integrates various aspects, but for red wines, it has a high correlation with accumulation of phenolics stimulated by UV-B and ABA.